Extreme actor. - Babcock, Tony; Babcock, Tony; Van Delft, Sydney (Academic Video Online, 2017)
Follow actor Tony Babcock as goes to the extreme while preparing for his auditions in this reality TV series with heart. Tony gets locked in a cell, trains as a Knight, investigates the paranormal, and more as he meets the real-life people behind the characters. All while answering the question: how extreme can one go to get into a role? Tony embarks on a journey of Knighthood at Medieval Times and takes a sword to the stomach in preparation for a big audition.